(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
A study was conducted to assess the existing bio-security practices in different live poultry markets in some selected areas of Bangladesh such as Dhaka City Corporation, Sirajgong Sadar and Sahjadpur Upazila from January 2015 to May 2015 using semi-structured and pre-tested questionnaire along with observation. A total number of one hundred twenty (120) respondents were purposively selected from the above mentioned locations. Forty (40) respondents were selected involved in live bird market and information collected from each area of markets to know the different contributing factors of live bird market bio-security situation through personal interviewing method. The results of the present study reveals that around seventy one percent (71%) live bird’s sellers used different type’s drugs to keep their birds sound and alive until sold out all birds. This study noticed that more than 71 percent respondents did not dispose the dead birds scientifically. The survey result showed that about fifty percent (50%) respondents used separate dress during working period at their sale centers. It was also observed that 87 percent respondents did not use commercial disinfectant to clean their dressing materials. Further it is noted that the sanitary and hygienic practices of the most live poultry sale centers were poor. This study clearly revealed that there was a high risk of disease transmission and dissemination both to poultry and human beings due to poor bio-security of live poultry markets in the study areas. It could be concluded that immediate necessary steps need to be undertaken by the government and other regulatory organizations to improve the live bird market situation for ensuring the safe poultry meat in the country. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 333-337